Al-‘Alāqah al-Mutabādilah Baina al-Īmān wa al-Jihād fī Sabīllilah - Muhammad Hirzin (Al-Jami'ah Research Centre, 1998)
The word “jihad' has been understood wrongly by some orientalists as a holly war. Amongst non-muslim societies this meaning is very influential that leads to a misperception that “jihad